Toner and two-component developer
Patent Information
- Application Number
- JP2021149721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-09
- Filing Date
- 2021-09-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-09-14
Smart Images

Figure 0007629830000003 
Figure 0007629830000004 
Figure 0007629830000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner and a two-component developer. [Background technology]
[0002] Toner (toner for developing electrostatic images) used in electrophotographic image forming devices such as copying machines, multifunction machines, printers, and facsimile machines usually has external additives attached to the surface of the toner particles. A charge control agent is an external additive that is added to control the chargeability of the toner.
[0003] Toners containing fine powder of strontium titanate as a charge adjusting agent have been known for some time (for example, Patent Document 1 and Patent Document 2). Patent Document 3 discloses an external toner additive in which strontium titanate-based fine particles that meet certain conditions are coated with alkoxysilane or the like.
[0004] Strontium titanate fine powder has a lower resistance than the toner mother particles (toner particles before external additives are added), and acts to propagate the negative charge locally charged on the toner surface to the surrounding toner particles or to release it into the air. Compared to toner without the addition of strontium titanate fine powder, the absolute value of the charge amount is smaller in both high and low humidity environments.
[0005] However, toners containing strontium titanate fine powder as a charge control agent have the problem that if the amount of fine powder added is increased, the absolute value of the charge amount in a high humidity environment becomes too small, making it difficult to control the image density and increasing fog. Conversely, if the amount of fine powder added is decreased, the absolute value of the charge amount in a low humidity environment becomes too large, and the charge amount difference between the toner in the developer and the replenishment toner becomes large, making it difficult for the replenishment toner to mix with the developer in the developer tank, and increasing fog due to scattering.
[0006] Therefore, in a toner containing fine powder of strontium titanate as a charge adjusting agent, there is a problem that the occurrence of fogging cannot be sufficiently suppressed in at least one of a low humidity environment and a high humidity environment. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 4594010 [Patent Document 2] Patent No. 4944980 [Patent Document 3] JP 2018-20919 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a toner and developer that contain fine powder of strontium titanate and that can suppress the occurrence of fogging in both low-humidity and high-humidity environments. [Means for solving the problem]
[0009] As a result of intensive research by the inventors to solve the above problems, they discovered that by adhering silica and fine powder made by hydrophobizing a core of strontium titanate with negatively charged silica added thereto with a silane compound to the surface of toner particles, the fog value can be kept low in both low humidity and high humidity environments, and thus completed the present invention.
[0010] That is, the toner according to the present invention is a toner having an external additive adhered to the surface of a toner particle, and is characterized in that the external additive contains silica and fine powder in which the surface of a core made of strontium titanate to which silica has been added is hydrophobized with a silane compound.
[0011] The developer according to the present invention is a developer containing the toner according to the present invention and a carrier, and is characterized in that the current value when a voltage of 300 V is applied from one end of a carrier magnetic brush having a length of 1 mm to the opposite end is 10 μA or less. Effect of the Invention
[0012] According to the present invention, it is possible to provide a toner and a developer that contain fine powder of strontium titanate and that can suppress the occurrence of fogging in both low-humidity and high-humidity environments. [Brief description of the drawings]
[0013] [Figure 1] 1 is a table showing fog values when strontium titanate is used as a charge control agent. [Diagram 2] 1 is a table showing fog values when silica-added strontium titanate is used as a charge control agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention includes toners and developers, which will be described in detail below.
[0015] [toner] The toner according to the present invention is a toner having an external additive attached to the surface of the toner particles. If necessary, the toner may further contain an optional component within a range that does not impair the effects of the present invention. The volume average particle diameter of the primary particles of the toner particles is not particularly limited, but examples thereof include toner particles having a volume average particle diameter of 4 μm or more and 8 μm or less.
[0016] Examples of the binder resin in the toner according to the present invention include polyester resins, polystyrene resins such as styrene-acrylic resins, (meth)acrylic acid ester resins, polyolefin resins, polyurethane resins, and epoxy resins. Among these, one type may be used alone, or two or more types may be used in combination.
[0017] <Binding resin> The polyester resin used for the binder resin is usually obtained by polycondensation reaction of one or more selected from a dihydric alcohol component and a trihydric or higher polyhydric alcohol component with one or more selected from a divalent carboxylic acid and a trivalent or higher polycarboxylic acid by a known method via an esterification reaction or an ester exchange reaction.
[0018] The conditions for the polycondensation reaction may be appropriately set depending on the reactivity of the monomer components, and the reaction may be terminated when the polymer has suitable physical properties. For example, the reaction temperature is about 170 to 250° C., and the reaction pressure is about 5 mmHg to normal pressure.
[0019] Examples of the dihydric alcohol component include alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane; Examples of the diols include glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; bisphenol A; propylene adducts of bisphenol A; ethylene adducts of bisphenol A; and hydrogenated bisphenol A.
[0020] Examples of trihydric or higher polyhydric alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, sucrose (cane sugar), 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0021] In the present invention, the above dihydric alcohol components and trihydric or higher polyhydric alcohol components may be used alone or in combination of two or more.
[0022] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, cyclohexanedicarboxylic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, n-dodecylsuccinic acid, n-octylsuccinic acid, isooctenylsuccinic acid, isooctylsuccinic acid, and acid anhydrides and lower alkyl esters thereof.
[0023] Examples of trivalent or higher polyvalent carboxylic acids include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, and acid anhydrides and lower alkyl esters thereof.
[0024] In the present invention, among the above divalent carboxylic acids and trivalent or higher polyvalent carboxylic acids, one kind may be used alone, or two or more kinds may be used in combination.
[0025] In the toner according to the present invention, the binder resin preferably contains a crystalline polyester resin and an amorphous polyester resin, and the crystalline polyester resin is dispersed in the amorphous polyester resin.
[0026] In the present invention, crystalline resins and amorphous resins are distinguished by their crystallinity index, with a resin having a crystallinity index in the range of 0.6 to 1.5 being crystalline resins, and a resin having a crystallinity index less than 0.6 or more than 1.5 being amorphous resins. Resins having a crystallinity index greater than 1.5 are amorphous, and resins having a crystallinity index less than 0.6 have low crystallinity and many amorphous portions.
[0027] The crystallinity index is a physical property that is an index of the degree of crystallization of a resin, and is defined by the ratio of the softening temperature to the highest endothermic peak temperature (softening temperature / highest endothermic peak temperature). Here, the highest endothermic peak temperature refers to the temperature of the highest endothermic peak among the observed endothermic peaks. In the case of a crystalline polyester resin, the highest peak temperature is the melting point, and in the case of an amorphous polyester resin, the highest endothermic peak is the glass transition point.
[0028] The degree of crystallization can be controlled by adjusting the types and ratio of raw material monomers, as well as production conditions (for example, reaction temperature, reaction time, cooling rate), and the like.
[0029] (Crystalline polyester resin) The crystalline polyester resin is a polyester resin having a crystallinity index of 0.6 to 1.5, preferably a polyester resin having a crystallinity index of 0.8 to 1.2. The crystalline polyester resin is obtained, for example, by polycondensation of a polybasic acid and a polyhydric alcohol. For example, it can be produced by a known method such as that described in JP-A-2006-113473.
[0030] Examples of polyhydric alcohols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, and 1,4-butenediol, but it is preferable to use a polyhydric alcohol that promotes the crystallinity of the resin, such as an aliphatic diol having 2 to 8 carbon atoms. These polyhydric alcohols may be used alone or in combination of two or more.
[0031] From the viewpoint of enhancing the crystallinity of the resin, the content of the aliphatic diol having 2 to 8 carbon atoms in the polyhydric alcohol is preferably 80 mol % or more, and when two or more kinds of aliphatic diols having 2 to 8 carbon atoms are used, the content of one kind of aliphatic diol having 2 to 8 carbon atoms in the polyhydric alcohol is desirably 70 mol % or more.
[0032] Examples of polybasic acids include aliphatic dicarboxylic acids having 2 to 30 carbon atoms, preferably 2 to 8 carbon atoms, such as fumaric acid, adipic acid, oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, sebacic acid, azelaic acid, n-dodecyl succinic acid, and n-dodecenyl succinic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid; and polyvalent carboxylic acids having three or more valences, such as trimellitic acid and pyromellitic acid. In order to obtain a high degree of crystallinity (crystallinity index), aliphatic dicarboxylic acids are preferred, and aliphatic dicarboxylic acids having 2 to 8 carbon atoms are more preferred. These polybasic acids may be used alone or in combination of two or more kinds.
[0033] The acid value of the crystalline polyester resin is preferably 5 mgKOH / g or more and 20 mgKOH / g or less, and the hydroxyl value of the crystalline polyester resin is preferably 5 mgKOH / g or more and 20 mgKOH / g or less.
[0034] The molecular weight of the crystalline polyester resin is preferably such that the weight average molecular weight (Mw) is from 5,000 to 100,000, and the number average molecular weight (Mn) is from 3,000 to 20,000. In the present invention, the weight average molecular weight and the number average molecular weight are values measured by gel permeation chromatography (GPC), in which chloroform is used as the mobile phase and polystyrene is used as the standard substance.
[0035] The softening temperature of the crystalline polyester resin is preferably 60° C. or higher and 105° C. or lower.
[0036] In the toner according to the present invention, the content of the crystalline polyester resin is not particularly limited, but is preferably 1% by mass or more and 20% by mass or less in the toner particles, and more preferably 2% by mass or more and 20% by mass or less. By making the content of the crystalline polyester resin equal to or more than the lower limit, it is possible to easily improve the low-temperature fixing property. By making the content of the crystalline polyester resin equal to or less than the upper limit, it is possible to easily improve the heat-resistant storage stability of the toner.
[0037] (Amorphous polyester resin) The amorphous polyester resin is a polyester resin having a crystallinity index of less than 0.6 or more than 1.5, and preferably a polyester resin having a crystallinity index of more than 1.5. The amorphous polyester resin is obtained, for example, by polycondensation of a polybasic acid and a polyhydric alcohol.
[0038] As the polybasic acid, known monomers for polyester synthesis can be used, and examples thereof include aromatic carboxylic acids such as terephthalic acid, isophthalic acid, phthalic anhydride, trimellitic acid, trimellitic anhydride, pyromellitic acid, and naphthalenedicarboxylic acid, aliphatic carboxylic acids such as maleic anhydride, fumaric acid, succinic acid, alkenyl succinic anhydride, and adipic acid, and methyl esters of these polybasic acids. These polybasic acids may be used alone or in combination of two or more.
[0039] As the polyhydric alcohol, known monomers for polyester synthesis can be used, and examples thereof include aliphatic polyhydric alcohols such as ethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, and glycerin, alicyclic polyhydric alcohols such as cyclohexanediol, cyclohexanedimethanol, and hydrogenated bisphenol A, and aromatic diols such as an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A. These polyhydric alcohols may be used alone or in combination of two or more.
[0040] The polycondensation reaction of the polybasic acid and the polyhydric alcohol can be carried out according to a conventional method, for example, by contacting the polybasic acid with the polyhydric alcohol in the presence or absence of an organic solvent and in the presence of a polycondensation catalyst (such as tin octylate), and the reaction is terminated when the acid value and softening temperature of the polyester produced reach the desired values. This results in an amorphous polyester resin. If a methyl ester of the polybasic acid is used as a part of the polybasic acid, a demethanol polycondensation reaction is carried out. In this polycondensation reaction, for example, the carboxyl group content at the end of the polyester can be adjusted by appropriately changing the blending ratio and reaction rate of the polybasic acid and the polyhydric alcohol, and thus the properties of the obtained amorphous polyester resin can be modified. In addition, if trimellitic anhydride is used as the polybasic acid, a carboxyl group can be easily introduced into the main chain of the polyester.
[0041] The polycondensation reaction between the polybasic acid and the polyhydric alcohol is usually carried out at a temperature of about 150° C. to 300° C., preferably about 170° C. to 280° C. The polycondensation reaction can be carried out under normal pressure, reduced pressure or increased pressure, and it is desirable to appropriately adjust the pressure in the system while monitoring the progress of the polycondensation reaction by monitoring physical property values (e.g., acid value, melting point, etc.) and the stirring torque or power value of the reactor.
[0042] The acid value of the amorphous polyester resin is preferably from 10 KOHmg / g to 30 KOHmg / g, and more preferably from 15 KOHmg / g to 25 KOHmg / g.
[0043] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 50,000 or less, and the number average molecular weight (Mn) is preferably 1,000 or more and 10,000 or less. In the present invention, the weight average molecular weight and the number average molecular weight are values measured by gel permeation chromatography (GPC), in which tetrahydrofuran (THF) is used as the mobile phase and polystyrene is used as the standard substance.
[0044] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 55°C or higher and 70°C or lower.
[0045] In the toner according to the present invention, the content of the amorphous polyester resin is not particularly limited, but is preferably from 67% by mass to 89% by mass in the toner particles.
[0046] <Other internal additives> Furthermore, the toner particles according to the present invention may contain a colorant, a charge control agent, a release agent, and the like. Components other than the external additives are also collectively called internal additives. As the colorant, organic dyes, organic pigments, inorganic dyes, inorganic pigments, and the like used in the field of electrophotography can be used. As the charge control agent, charge control agents for positive charge control and negative charge control used in the field of electrophotography can be used. As the release agent, wax used in the field of electrophotography can be used.
[0047] <External additives> In the present invention, the external additive contains silica and fine powder in which the surface of a core made of strontium titanate with silica added thereto is hydrophobized with a silane compound. By containing the fine powder and silica, the toner according to the present invention can suppress the occurrence of fogging in both low humidity and high humidity environments. In this specification, the toner according to the present invention having toner particles with an external additive attached to the surface is appropriately referred to as an external additive toner. In addition, a core made of strontium titanate with silica added thereto and the surface of which is hydrophobized with a silane compound may be referred to as silica-added strontium titanate.
[0048] In the toner of the present invention, the molar ratio Si / Ti of silicon to titanium in the fine powder is preferably 0.03 or more and less than 1.0, more preferably 0.04 or more and 0.06 or less. Si / Ti represents the content ratio of silica in the fine powder. If Si / Ti is less than the lower limit, the negative chargeability is weakened, and the chargeability is reduced in a high humidity environment, which may increase the fog value. If Si / Ti exceeds the upper limit, the negative chargeability is strengthened, and the adhesion force between the toner and the carrier is increased due to the chargeability increase in a low humidity environment, so that the toner supplied later is difficult to mix and is not sufficiently charged when developed, which may result in increased toner scattering and increased fog value.
[0049] In the toner according to the present invention, the coverage of the fine powder on the toner particle surface is preferably 2% or more and 10% or less. By having the coverage of the fine powder within the above range, the fog value can be kept low in low humidity and high humidity environments. If the coverage of the fine powder is below the lower limit, the fog value in a low humidity environment may be large. On the other hand, if the coverage of the fine powder exceeds the upper limit, the fog value in a high humidity environment may be large.
[0050] In the toner according to the present invention, the coverage of the toner particle surface with the silica is preferably 40% or more. By having the coverage of the silica with 40% or more, the fogging value in a high humidity environment can be suppressed to a low level. The total coverage of the toner particle surface with the silica and the fine powder is 100% or less.
[0051] In the toner according to the present invention, the ratio A of the adhesion strength of the fine powder to the adhesion strength of the silica, calculated by the following formula (1), is preferably 1.1 or less. If the adhesion strength ratio A exceeds 1.1, there is a risk of high humidity fogging becoming worse. A=(adhesive strength of the silica) / (adhesive strength of the fine powder) (1)
[0052] The adhesion strength ratio A is more preferably 0.7 or more and 1.1 or less. It is even more preferably 0.8 or more and 1.1 or less. If the adhesion strength ratio A is less than the lower limit, there is a risk of high humidity fogging becoming worse. The adhesion strength ratio A indicates the proportion of the external additive embedded in the surface of the toner base particle, and the environmental charging performance is most exhibited within the above range. If the adhesion strength ratio A exceeds the upper limit, there is a risk of the environmental charging performance being lost due to the fine powder being strongly embedded.
[0053] In the toner according to the present invention, the resistance change D of the toner calculated by the following formula (2) is preferably −10 or more. If the resistance change D of the toner is less than −10, high-humidity fogging may not be improved. D = (BC) / (bc) (2) (In formula (2), B is the resistance value (GΩ) of the toner when b parts by mass of fine powder is added to 100 parts by mass of toner particles. C is the resistance value (GΩ) of the toner when c parts by mass of fine powder is added to 100 parts by mass of toner particles.)
[0054] The toner resistance change amount D is more preferably from −10 to −3, and even more preferably from −10 to −8. If the toner resistance change amount D exceeds the upper limit, low-humidity fogging may not be improved.
[0055] If the dispersion of the fine powder becomes poor, the change in resistance value relative to the change in the amount of the fine powder added becomes large, and the environmental charging performance of the fine powder may be lost.
[0056] The fine powder obtained by hydrophobizing the surface of a core of strontium titanate with silica added thereto with a silane compound preferably has an average primary particle diameter of 20 nm or more and 60 nm or less. More preferably, it is 30 nm or more and 50 nm or less. By having the average primary particle diameter of the fine powder within the above range, the fog value in a low humidity environment and a high humidity environment can be kept small. If the average primary particle diameter of the fine powder is less than the above lower limit, the fog value in a high humidity environment may be large. On the other hand, if the average primary particle diameter of the fine powder exceeds the above upper limit, the fog value in a low humidity environment may be large.
[0057] In the toner according to the present invention, it is preferable that the toner contains, as an external additive, 0.1 parts by mass or more and 0.6 parts by mass or less of zinc stearate fine particles having an average primary particle diameter of 0.5 μm or more and 3 μm or less. By adding zinc stearate as an external additive, the environmental charging performance of the toner can be further improved, and the cleaning performance of the toner placed on the photoconductor drum can also be improved. More preferably, the average primary particle diameter of the zinc stearate fine particles is 0.6 μm or more and 2.5 μm or less, and the content is 0.2 parts by mass or more and 0.5 parts by mass or less. If the average primary particle diameter or content of the zinc stearate fine particles is outside the above range, the cleaning performance of the toner placed on the photoconductor drum may not be improved. In addition, the environmental charging performance of the toner may not be improved.
[0058] The fine powder in which the surface of a core made of strontium titanate to which silica has been added is hydrophobized with a silane compound can be produced, for example, by the following procedures (1) to (5). (1) Metatitanic acid obtained by the sulfuric acid method is deironized and bleached, then desulfurized by adding an aqueous solution of sodium hydroxide, and then neutralized with hydrochloric acid. After filtration and washing with water, a washed cake is obtained. (2) Water is added to the washed cake to make a slurry, and then hydrochloric acid is added to perform a peptization treatment. This is solution 1, and is mixed with solution 2, an aqueous solution of strontium chloride, and solution 3, an aqueous solution of sodium silicate. The mixing ratio of solutions 1, 2, and 3 is set so that the molar ratio of (Sr+Si) / Ti is within the range of 1.18 to 2.10. (3) The mixed solution is heated to 90°C under a nitrogen gas atmosphere, and an aqueous sodium hydroxide solution is added while stirring for 2 hours to complete the reaction. (4) After the reaction, the slurry is cooled to 50°C, hydrochloric acid is added and stirred for 2 hours. The resulting precipitate is washed, separated by filtration, and then dried. (5) The dried product is ground in a blender for 1 minute, and the coarse powder is removed using a sieve with a mesh size of 32 μm. The resulting fine powder substrate is then surface-coated with a silane coupling agent. Examples of methods for surface-coating with a silane coupling agent include surface treatments commonly used in the art using hexamethyldisilazane (HMDS), dimethyldichlorosilane (DDS), octylsilane (OTAS), polydimethylsiloxane (PDMS), etc.
[0059] The silica as an external additive in the present invention is not particularly limited, but examples thereof include WACKER's product name "H2000T" in which fumed silica having an average particle size of 12 nm is surface-treated with hexamethyldisilazane, EVONIK's product name "R974" in which fumed silica having an average particle size of 12 nm is surface-treated with dimethyldichlorosilane, EVONIK's product name "RX200" in which fumed silica having an average particle size of 12 nm is surface-treated with hexamethyldisilazane, and EVONIK's product name "R976S" in which fumed silica having an average particle size of 7 nm is surface-treated with dimethyldichlorosilane.
[0060] [Developer] The developer according to the present invention contains the toner according to the present invention and a carrier. The developer can be produced by mixing the toner and the carrier using a known mixer. The weight ratio of the toner to the carrier is not particularly limited, and may be, for example, 3:97 to 12:88.
[0061] The carrier is stirred and mixed with the toner in the developing tank, giving the toner a desired charge. The carrier also acts as an electrode between the developing device and the photoconductor, carrying the charged toner to the electrostatic latent image on the photoconductor to form a toner image. The carrier is held on the developing roller of the developing device by magnetic force, and after acting in development, it returns to the developing tank, where it is stirred and mixed with new toner again and is used repeatedly until the end of its life.
[0062] The carrier has a carrier core material and a resin coating layer that coats the carrier core material. The carrier core material is not particularly limited as long as it is used in the electrophotographic field. Specific examples of the material of the carrier core material include magnetic metals such as iron, copper, nickel, and cobalt, and magnetic metal oxides such as ferrite and magnetite. The volume average particle size of the carrier core material is not particularly limited, and may be, for example, 30 μm or more and 100 μm or less. The resin coating layer preferably contains a silicone resin or an acrylic resin. Silicone resin can delay the progression of contamination of the carrier coat layer, and is suitable for long-life use.
[0063] The developer according to the present invention has a current value of 10 μA or less when a voltage of 300 V is applied from one end of a carrier magnetic brush having a length of 1 mm to the other end of the brush. More preferably, it is 9 μA or less. By keeping the current value below the upper limit, the fog value in a high humidity environment can be kept low. By using a carrier having a high resistance value compared to a toner that does not use the fine powder, a developer with a low fog value can be produced. When the current value is within the upper limit, the fog value does not increase within the range in which the toner is normally developed.
[0064] The present invention will be described below based on examples and comparative examples, but the present invention is not limited to these examples. First, measurements in the examples will be described.
[0065] <Method for measuring the coverage rate of external additives> The toner with external additives was photographed with a scanning electron microscope (SEM) (Hitachi High-Technologies Corporation, Model: S-4800). A model calculation was performed using the average particle size and specific gravity of the toner particles (toner parent particles) and the average particle size and specific gravity of each external additive, and the coverage rate of each external additive was calculated using the following formula (3).
[0066]
number
[0067] In the above formula (3), D is the average particle diameter of the toner particles, ρ t is the specific gravity of the toner particles, d is the average particle diameter of the external additive, ρ i is the specific gravity of the external additive, and C is the number of parts by mass of the external additive added.
[0068] <Method for measuring adhesive strength of external additives> The adhesion strength of each external additive to the toner particles (toner base particles) was measured by the following procedure. Note that the silica in the expression "adhesion strength of silica" does not refer to silica added to the core of the fine powder, but to silica added as an external additive to the toner (not part of the fine powder). (1) 2.0 g of toner is added to 40 ml of a 0.2% by mass aqueous solution of Triton (polyoxyethylene octylphenyl ether), and the mixture is stirred for 1 minute. (2) The above aqueous solution is irradiated with ultrasonic waves using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., model: US-300T) (output: 40 μA, 4 minutes). (3) The aqueous solution after the ultrasonic irradiation is left to stand for 3 hours, and the toner and the liberated external additives are separated. (4) After removing the supernatant, add approximately 50 ml of pure water to the precipitate and stir for 5 minutes. (5) The mixture is subjected to suction filtration using a membrane filter having a pore size of 1 μm (manufactured by Advantec Co., Ltd.). (6) The toner remaining on the filter is vacuum dried overnight. (7) Using an X-ray fluorescence analyzer (Rigaku Corporation, model: ZSX Primus II), the intensities of the elements (Si) and (Ti) in the external additive of 1 g of toner before and after the series of processes (1) to (6) above are analyzed, and the adhesion strength of the external additive is calculated using the following formula. Silica adhesion strength (%) = {(Si strength after treatment) / (Si strength before treatment)} x 100 Adhesion strength (%) of fine powder in which the surface of a core made of strontium titanate with silica added is hydrophobized with a silane compound = {(Ti strength after treatment) / (Ti strength before treatment)} x 100
[0069] In addition, the amount of silica added to the core of the above fine powder is about 2 to 10 mol relative to strontium titanate, so as described above, the adhesion strength of the fine powder was calculated based on the intensity of the Ti element measured with an X-ray fluorescence analyzer.
[0070] Then, the ratio A of the adhesive strength of the fine powder to the adhesive strength of silica was calculated by the following formula (1). A = (adhesive strength of silica) / (adhesive strength of fine powder) (1)
[0071] <Method of measuring toner resistance> 1 g of toner was placed in a φ25 mm container and compressed for 20 seconds at a force of 20 MPa to obtain a solid sample with a diameter of 25 mm and a thickness of 2 mm. The resistance of the toner was measured using a 2550A capacitance bridge (manufactured by Andeen-Hagerling).
[0072] Using the resistance value obtained by this measurement, the amount of change D in the resistance value of the toner was calculated according to the following formula (2). D = (BC) / (bc) (2) (In formula (2), B is the resistance value (GΩ) of the toner when b parts by mass of the fine powder is added to 100 parts by mass of toner particles. C is the resistance value (GΩ) of the toner when c parts by mass of the fine powder is added to 100 parts by mass of toner particles.)
[0073] <How to output printed materials> A color multifunction printer (model: MX-3631, manufactured by Sharp Corporation) was used as the evaluation machine. The evaluation machine was operated in an environmental testing room under a low humidity environment (temperature 25°C, relative humidity 5%) and a high humidity environment (temperature 25°C, relative humidity 80%), and 10,000 sheets of an image in which 10% of the printable area of A4 paper was filled with cyan toner were printed.
[0074] <Method of measuring the cover value> As described above, an image was printed in which 10% of the printable area of A4 paper was filled with cyan toner using an evaluation machine (Model: MX-3631, manufactured by Sharp Corporation), and the brightness of a specific area of the image that was not filled was measured using a colorimeter (Model: ZE6000, manufactured by Nippon Denshoku Industries Co., Ltd.). The difference between this brightness and the brightness measured before printing was taken as the overcast value.
[0075] <How to evaluate the cover value> The samples of the Examples and Comparative Examples were placed in the above-mentioned evaluation machine, and the fog values were measured and evaluated in a high humidity environment and a low humidity environment as described below.
[0076] The fog value of the first sheet after printing was measured, then 9998 sheets were printed at a print rate of 1%, and the fog value of the 10,000th sheet was measured. The fog value was then evaluated according to the following criteria. The specified fog value refers to a specified value determined by the evaluation machine and the evaluation content. ◎: Excellent (measured value is 80% or less of the specified fogging value) 〇: Good (measured value is more than 80% and less than 90% of the specified value of fog value) △: Passable (The measured value is more than 90% and less than 100% of the specified fogging value) ×: Unacceptable (measured value is more than 100% of the specified fogging value)
[0077] In Example 12 in Table 1 shown later, the specified value was 2.0, and the fog value of the first sheet in a high humidity environment was 0.9, so the measured value was 45%, and the result was evaluated as "Excellent".
[0078] Based on these four evaluations (the first sheet under high humidity environment, the 10,000th sheet under high humidity environment, the first sheet under low humidity environment, and the 10,000th sheet under low humidity environment), an overall evaluation of the fog value was made according to the following criteria. ◎: Excellent (all four ratings are ◎ or 〇, with three or more being ◎) 〇: Good (all four ratings are ◎ or 〇, with two or less ◎ ratings) △: Passable (none of the four evaluations is ×, and one is △) ×: Unacceptable (any of the four evaluations is ×)
[0079] [Production of toner particles] The toner particles (toner base particles) used in the examples and comparative examples were prepared as follows.
[0080] First, the following materials were premixed for 5 minutes using an airflow mixer (Henschel mixer, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke and Engineering Co., Ltd.), model: FM20C) [mixing process]. Binder resin: Amorphous polyester resin 67% by weight Crystalline polyester resin 20% by mass Colorant: CI Pigment Blue 15:3 (DIC Corporation) 7% by weight Release agent: Monoester wax (NOF Corporation, product name: WEP-3) 5% by mass Charge control agent: Salicylic acid compound (Orient Chemical Industry Co., Ltd., product name: Bontron E-84) 1% by mass
[0081] Next, the mixture was melt-kneaded using an open roll type continuous kneader (manufactured by Mitsui Mining Co., Ltd. (currently Nippon Coke and Engineering Co., Ltd.), model: MOS320-1800) to obtain a molten kneaded product [kneading process].
[0082] The open roll conditions were as follows: heating roll supply side temperature 130° C., discharge side temperature 100° C., cooling roll supply side temperature 40° C., discharge side temperature 25° C. The heating roll and cooling roll had a diameter of 320 mm and an effective length of 1550 mm, and the gap between the rolls on both the supply side and discharge side was 0.3 mm. The rotation speed of the heating roll was 75 rpm, the rotation speed of the cooling roll was 65 rpm, and the supply amount of the toner raw material was 5.0 kg / h.
[0083] The resulting molten mixture was cooled with a cooling belt, and then coarsely pulverized using a speed mill with a φ2 mm screen to obtain a coarsely pulverized product. The coarsely pulverized product was finely pulverized using a jet pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd., model: IDS-2) to obtain a finely pulverized product [fine pulverization process].
[0084] Next, the resulting finely pulverized material was classified using an elbow jet classifier (manufactured by Nittetsu Mining Co., Ltd., model: EJ-LABO) to obtain toner particles [classification step].
[0085] [Addition of external additives to toner particles] As described below, the external additives were added to the toner particles in a first addition step and a second addition step, and the external additives were adhered to the surfaces of the toner particles.
[0086] (Examples 8 and 12) First, in Table 1 below, we will explain the process of adding external additives in Examples 8 and 12, in which the silica coverage is 90%, the silica-added strontium titanate fine powder coverage is 10%, the adhesion strength ratio A is 0.9, and the resistance change is -10.
[0087] In the first addition step, 100 parts by mass of toner particles and 1.3 parts by mass of silica (manufactured by WACKER, product name: H2000T) were added to a container, and the contents of the container were mixed at a rotation speed of 2700 rpm for 2 minutes using an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd., product name: FM-20).
[0088] Next, in the second addition step, 1.0 part by mass of fine powder in which the surface of a core made of strontium titanate with silica added thereto was hydrophobized with a silane compound was added to the container, and mixed for 2.2 minutes at a rotation speed of 2700 rpm using an FM mixer to obtain a mixture. This mixture was sieved using a 270 mesh sieve to obtain an externally added toner.
[0089] In addition, when zinc stearate microparticles are used as an additional external additive, in the third external addition process, 0.4 parts by mass of zinc stearate microparticles having an average primary particle diameter of 1 μm are added to the above container and mixed for 1 minute at a rotation speed of 2700 rpm using an FM mixer to obtain a mixture, which is then sieved using a 270 mesh sieve to obtain a toner with externally added zinc stearate microparticles.
[0090] The fine powder used in the second addition step was produced according to the following steps (1) to (5). (1) Metatitanic acid obtained by the sulfuric acid method was deironized and bleached, then desulfurized by adding an aqueous solution of sodium hydroxide, and then neutralized with hydrochloric acid. After filtration and washing with water, a washed cake was obtained. (2) Water was added to the washed cake to make a slurry, and then hydrochloric acid was added to perform a peptization treatment. This was solution 1, and was mixed with solution 2, an aqueous solution of strontium chloride, and solution 3, an aqueous solution of sodium silicate. The mixing ratio of solutions 1, 2, and 3 was set so that the molar ratio of (Sr+Si) / Ti was 1.2. (3) The mixed solution was heated to 90°C under a nitrogen gas atmosphere, and an aqueous sodium hydroxide solution was added while stirring for 2 hours to complete the reaction. (4) After the reaction, the slurry was cooled to 50°C, hydrochloric acid was added, and the mixture was stirred for 2 hours. The resulting precipitate was washed, separated by filtration, and then dried. (5) The obtained dried material was pulverized in a blender for 1 minute, and after removing coarse powder with a sieve having an opening of 32 μm, the obtained fine powder substrate was subjected to a DDS surface coating with a silane coupling agent.
[0091] In addition, when "R976S" is used instead of "H2000T" as the silica to be added in the first addition step, the amount to be added can be determined using the above formula (3), and in the above case, it should be 0.7 parts by mass.
[0092] (Examples 1 to 5, 9 to 11, 17 to 20) For Examples 1 to 5, 9 to 11, and 17 to 20, which have an adhesion strength ratio A of 0.9 and a resistance change of -10 like Examples 8 and 12, the number of parts of external additive added was changed to that calculated using the above formula (3) so that the coverage rate became the value shown in Table 1, and external additive toner was obtained in the same manner as Examples 8 and 12.
[0093] Example 6 In Example 6, in which the adhesion strength ratio A was 1.2, the mixing time in the first addition step was changed to 3 minutes, and otherwise the same procedures as in Examples 8 and 12 were carried out to obtain a toner with external additives.
[0094] Example 7 In Example 7, in which the resistance change amount D was −12, the mixing time in the first addition step was changed to 1.3 minutes, and the mixing time in the second addition step was changed to 1.4 minutes, and otherwise an external additive toner was obtained in the same manner as in Examples 8 and 12.
[0095] Example 13 In Example 13, in which the adhesion strength ratio A was 1.1, the mixing time in the first addition step was changed to 2.2 minutes, and otherwise the same procedures as in Examples 8 and 12 were carried out to obtain a toner containing an external additive.
[0096] Example 14 In Example 14, in which the adhesion strength ratio A was 0.6, the mixing time in the first addition step was changed to 1.9 minutes, and otherwise the same procedures as in Examples 8 and 12 were carried out to obtain a toner with external additives.
[0097] Example 15 In Example 15, in which the resistance change amount D was −9, the mixing time in the first addition step was changed to 1.8 minutes, and the mixing time in the second addition step was changed to 2 minutes, and otherwise an external additive toner was obtained in the same manner as in Examples 8 and 12.
[0098] (Example 16) In Example 16, in which the resistance change amount D was -2, the mixing time in the first addition step was changed to 2.5 minutes, and the mixing time in the second addition step was changed to 2.8 minutes, and otherwise an external additive toner was obtained in the same manner as in Examples 8 and 12.
[0099] Example 21 In Example 21, an external additive toner was obtained in the same manner as in Example 12, except that a fine powder was used in which the mixing ratio of Solution 1, Solution 2, and Solution 3 in (2) of the above fine powder manufacturing procedure was changed so that the molar ratio of (Sr+Si) / Ti was 1.18.
[0100] Example 22 In Example 22, an external additive toner was obtained in the same manner as in Example 12, except that a fine powder was used in which the mixing ratio of Solution 1, Solution 2, and Solution 3 in (2) of the above fine powder manufacturing procedure was changed so that the molar ratio of (Sr+Si) / Ti was 2.10.
[0101] (Example 23) In Example 23, an external additive toner was obtained in the same manner as in Example 12, except that a fine powder was used in which the mixing ratio of Solution 1, Solution 2, and Solution 3 in (2) of the above fine powder manufacturing procedure was changed so that the molar ratio of (Sr+Si) / Ti was 1.16.
[0102] (Example 24) In Example 24, an external additive toner was obtained in the same manner as in Example 12, except that a fine powder was used in which the mixing ratio of Solution 1, Solution 2, and Solution 3 in (2) of the above fine powder manufacturing procedure was changed so that the molar ratio of (Sr+Si) / Ti was 2.16.
[0103] (Comparative Examples 1 to 8) In Comparative Examples 1 to 8, strontium titanate was used as an external additive instead of fine powder in which a core having silica added to strontium titanate was subjected to hydrophobic treatment with a silane compound on the surface, and the amount of the external additive added was changed to the amount calculated using the above formula (3) so that the coverage rate was the value shown in Table 1. Except for this, an externally-added toner was obtained in the same manner as in Examples 8 and 12.
[0104] [Carrier manufacturing] A resin liquid was prepared by adding 10 parts by weight of PTFE (manufactured by Daikin Industries, Ltd., product name: LDE-410) as fluororesin microparticles to 100 parts by weight of silicone resin, and a carrier core material was immersed in this resin liquid to obtain carrier "SC-1."
[0105] Similarly, 12 parts by weight of PTFE (manufactured by Daikin Industries, Ltd., product name: LDE-410) as fluororesin microparticles was added to 100 parts by weight of silicone resin to prepare a resin liquid, and a carrier core material was immersed in this resin liquid to obtain carrier "SC-2."
[0106] [Measurement of current value when voltage is applied from one end of the carrier magnetic wire to the other end] A jig was used, in which two 1 mm thick stainless steel plates were placed in parallel with a gap of 1 mm on a phenolic resin base. 0.2 g of the obtained carrier was placed between the two stainless steel plates, and two 100 mT anisotropic ferrite magnets were sandwiched from the outside of the stainless steel plates with the north and south poles facing each other, forming magnetic chains of the carrier between the stainless steel plates. Wiring was applied to the two stainless steel plates, and an electrometer (Advantest, model: R8340) was connected to measure the current value when 300 V was applied.
[0107] The current value of the carrier "SC-1" was 10 μA, and the current value of the carrier "SC-2" was 8 μA.
[0108] [Preparation of developer] In Examples 1 to 10, 13 to 20 and Comparative Examples 1 to 6, the obtained externally added toner and carrier "SC-1" were mixed in a V-type mixer (manufactured by Tokuju Machine Works, Ltd., model: V-5) for 20 minutes so that the toner concentration was 7% by mass to prepare a two-component developer.
[0109] In Examples 11 to 12, 21 to 24 and Comparative Examples 7 to 8, the obtained externally added toner and carrier "SC-2" were mixed in a V-type mixer (manufactured by Tokuju Machine Works, Ltd., model: V-5) for 20 minutes so that the toner concentration was 7% by mass to prepare a two-component developer.
[0110] The evaluation results of the toners and developers thus prepared according to the examples and comparative examples are shown in Table 1 below.
[0111] [Table 1]
[0112] As is clear from Table 1, the toners and developers of Examples 1 to 24, which contain silica as an external additive and a fine powder in which the surface of a core made of strontium titanate to which silica has been added is hydrophobized with a silane compound, were evaluated to have excellent fog values in both low-humidity and high-humidity environments.
[0113] In contrast, Comparative Examples 1 to 8, which did not satisfy these requirements, were inferior to the Examples in the evaluation of fog value in at least one of a low humidity environment and a high humidity environment.
[0114] Also, for example, referring to Examples 11 and 12, it can be seen that in Example 11, in which the surface of a core in which silica is added to strontium titanate is hydrophobized with a silane compound and the coverage of the fine powder is low (the amount of fine powder added is reduced), and in Example 12, in which the coverage of the fine powder is high (the amount of fine powder added is increased), the evaluation of the fogging value is excellent in both low humidity and high humidity environments. In other words, Example 11 corresponds to the case in which the amount of charge control agent added in Figure 2 is reduced, and Example 12 corresponds to the case in which the amount of charge control agent added is increased. Note that the type and amount of silica (silica that is not part of the fine powder) added together with the charge control agent are the same in the cases where the amount of charge control agent added in Figure 2 is reduced and increased.
[0115] On the other hand, referring to Comparative Example 7 and Comparative Example 8, in Comparative Example 7 where the coverage of strontium titanate is low (the amount of strontium titanate added is reduced), the evaluation of the fogging value of the 10,000th sheet in a low humidity environment is "x", and in Comparative Example 8 where the coverage of strontium titanate is high (the amount of strontium titanate added is increased), the evaluation of the fogging value of the first sheet in a high humidity environment is "x". In other words, Comparative Example 7 corresponds to the case where the charge control agent in FIG. 1 is reduced, and Comparative Example 8 corresponds to the case where the charge control agent is increased. Note that the type and amount of silica (silica that is not a part of the fine powder) added together with the charge control agent are the same in the cases where the amount of charge control agent added in FIG. 1 is reduced and increased.
[0116] Next, when focusing on the adhesive strength ratio A, it can be seen that in Example 6, where A exceeds 1.1, the evaluation of the first sheet in a high humidity environment was "△". On the other hand, in Example 13, where A is in the range of 0.7 to 1.1, it can be seen that the evaluation of the first sheet in a high humidity environment improved from "△" to "○" compared to Example 6.
[0117] Also, in Example 14, where A is less than 0.7, the evaluation of the first sheet in a high humidity environment was "△". On the other hand, in Example 5, where A is in the range of 0.7 to 1.1, the evaluation of the first sheet in a high humidity environment was improved from "△" to "○" compared to Example 14.
[0118] Furthermore, when focusing on the amount of change in resistance value D, it can be seen that in Example 7, where D is less than -10, the evaluation of the 10,000th sheet in a low humidity environment was "△". On the other hand, in Example 15, where D is in the range of -10 to -3, the evaluation of the 10,000th sheet in a low humidity environment improved from "△" to "◎" compared to Example 7.
[0119] In addition, Example 16, in which D exceeds -3, and Example 5, in which D is within the range of -10 to -3, are both evaluated as "Good" on the 10,000th sheet under a low humidity environment, but it can be seen that the fogging value of Example 5 is improved compared to Example 16.
[0120] In Examples 21 to 24, the amount of silica added in the fine powder obtained by adding silica to strontium titanate and hydrophobizing the surface of the core with a silane compound was changed from that of Example 12.
[0121] In Examples 21 and 23, in which the amount of silica added was reduced from that in Example 12, the fine powder had an angular shape, and the adhesion strength of the fine powder tended to be slightly higher. On the other hand, in Examples 22 and 24, in which the amount of silica added was increased from that in Example 12, the fine powder had a rounded shape, and the adhesion strength of the fine powder tended to be slightly lower. Note that, although the powder resistivity tends to increase when the silica content in the fine powder is increased, the change in resistance D is not significant within the range of Examples 21 to 24 (Si / Ti range of 0.03 to 1.0).
[0122] Focusing on Examples 12, 21, and 23, it can be seen that Examples 12 and 21, in which Si / Ti is 0.03 or more, are superior in the evaluation of the first sheet, especially in a high humidity environment, compared to Example 23, in which Si / Ti is 0.01.
[0123] Furthermore, looking at Examples 12, 22 and 24, it can be seen that Examples 12 and 22, in which Si / Ti is less than 1.0, are superior to Example 24, in which Si / Ti is 1.0, in the evaluation of the 10,000th sheet, especially in a low humidity environment.
[0124] In Example 24, in which the amount of silica added to the fine powder was increased, the silica precipitated on the surface of the fine powder and became particulate, increasing the circularity and decreasing the adhesive strength of the fine powder. It can be seen that the negative chargeability of Example 24 was further increased by increasing the amount of silica added to the fine powder and by the precipitation of silica on the surface of the fine powder, and the fog value in a low humidity environment was greatly increased.
[0125] <Other embodiments> It should be noted that the embodiments disclosed herein are illustrative in all respects and are not intended to be limiting. Therefore, the technical scope of the present invention is not interpreted solely by the above-described embodiments, but is defined by the claims. The technical scope of the present invention includes all modifications within the scope and meaning equivalent to the claims.
Claims
1. A toner having an external additive attached to the surface of a toner particle, The external additive contains a fine powder obtained by hydrophobizing a surface of a core formed by adding silica to strontium titanate with a silane compound, and silica having an average particle size of 7 nm or more and 12 nm or less, the coverage of the toner particle surface with the silica is 60% or more, The toner, wherein the total of the coverage of the toner particle surface with the silica and the coverage of the fine powder is 70% or more and 100% or less.
2. 2. The toner according to claim 1, The toner according to the present invention is characterized in that the molar ratio of silicon to titanium in the fine powder, Si / Ti, is 0.03 or more and less than 1.
0.
3. The toner according to claim 1 or 2, The toner, wherein the coverage of the toner particle surface with the fine powder is 2% or more and 10% or less.
4. The toner according to any one of claims 1 to 3, The toner according to claim 1, wherein a ratio A of the adhesive strength of the fine powder to that of the silica, calculated by the following formula (1), is 1.1 or less: A=(adhesive strength of the silica) / (adhesive strength of the fine powder) (1)
5. The toner according to any one of claims 1 to 4, A toner characterized in that a change in resistance value D of the toner calculated by the following formula (2) is −10 or more: D=(B-C) / (b-c)...(2) (In formula (2), B is the resistance value (GΩ) of the toner when b parts by mass of the fine powder are added to 100 parts by mass of the toner particles. C is the resistance value (GΩ) of the toner when c parts by mass of the fine powder are added to 100 parts by mass of the toner particles.)
6. The toner according to any one of claims 1 to 5, The toner is characterized in that the average primary particle diameter of the fine powder is 20 nm or more and 60 nm or less.
7. A developer comprising the toner according to any one of claims 1 to 6 and a carrier, A developer characterized in that a current value when a voltage of 300 V is applied from one end of a carrier magnetic brush having a length of 1 mm to the other end of the brush is 10 μA or less.
Citation Information
Patent Citations
JP1974044980A
Toner
JP2015028601A
Toner
JP2016102904A
Strontium titanate-based fine particle for toner and manufacturing method therefor
JP2018020919A
Electrostatic charge image developer, process cartridge, image forming apparatus, and image forming method
JP2020046578A